Phospha derivatives of tris(2-aminoethyl)amine (tren) and tris(3-aminopropyl)amine (trpn): synthesis and complexation studies with group 4 metals - Sietzen, Malte; Batke, Sonja; Merz, Lukas; Wadepohl, Hubert; Ballmann, Joachim (Organometallics, 2015)
The N,N′,N″-triphenyl-substituted derivative of tris(2-aminoethyl)phosphine (Ph3-phospha-tren, P(CH2CH2NHR)3, R = Ph) and four derivatives of the related tris(3-aminopropyl)phosphine (phospha-trpn, P(CH2CH2CH2NHR)3, R = iPr, tBu, SitBuMe2, Ph) have been synthesized in addition to the parent phospha-trpn. Out of these ligand systems, only the N,N′,N″-triphenyl-substituted phospha-trpn derivative P(CH2CH2CH2NHPh)3 was found to be suitable for coordination to group 4 metals. For titanium, zirconium, and hafnium, the C3-symmetric endo-P-configured dimethylamido complexes Ph[PN3]M(NMe2) of the former ligand have been prepared and converted into the corresponding triflates Ph[PN3]M(OTf). Starting from these triflates, the benzyl complexes Ph[PN3]M(Bn) (M = Ti, Zr, Hf) have been obtained via reaction with Bn2Mg(THF)2. In case of titanium, the benzyl species Ph[PN3]Ti(Bn) is prone to thermal elimination of toluene, which results in the formation of a cyclometalated species. These findings are discussed in context with the very few group 4 trisamidophosphine complexes that have been reported earlier.
Gesehen am 17.06.2020